The Way of Kinship : An Anthology of Native Siberian Literature - Smith, Claude Clayton, 1944-; Vashchenko, A. (Aleksandr) (Book collections on Project MUSE., 2010)
That these treasures are available to us as writing is a miracle. ... The writings here, while altogether modern in one sense, are based upon a literature, albeit oral, that has existed for thousands of years. They are the reflections of people who have lived long on the earth, on their own terms, in harmony with the powers of nature. They are invaluable to us who have so much to learn from them. These stories, poems, songs give us a way, a sacred way, into a world that we ought to know for its own sake. It is our own world, after all.-N. Scott Momaday, from the Foreword The first anthology.